The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1756-0500-7-361
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the self-reported hearing questions in the Irish Longitudinal Study on Ageing against the Whispered Voice Test

Abstract: BackgroundSelf report questions are often used in population studies to assess sensory efficacy and decline. These questions differ in their validity in assessing sensory impairment depending on the wording of the question and the characteristics of the population. We tested the validity of the self-report questions on hearing efficacy (self reported hearing, ability in following a conversation, use of a telephone and use of hearing aids) used in The Irish Longitudinal Study on Ageing (TILDA).MethodsWe tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 25 publications
0
17
1
Order By: Relevance
“…As previously reported by the authors [13], the prevalence rate of presbycusis, identified by means of the WVT, was 13.6% in our sample. This estimate is lower than that reported by the World Health Organization on the basis of audiometric evaluation [22], but higher than the 10.7% reported in another study population in which the WVT was administered [23].…”
Section: Discussioncontrasting
confidence: 73%
“…As previously reported by the authors [13], the prevalence rate of presbycusis, identified by means of the WVT, was 13.6% in our sample. This estimate is lower than that reported by the World Health Organization on the basis of audiometric evaluation [22], but higher than the 10.7% reported in another study population in which the WVT was administered [23].…”
Section: Discussioncontrasting
confidence: 73%
“…They are also characterized as faster and more economical surveys to provide population estimates, since they minimize fieldwork time and costs with equipment and trained professionals [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Especially, self-rated perception-related questionnaires by retirees with poor health might also have bias. While the KLoSA applied computer-assisted interviews by trained researchers to reduce these errors, these limitations are not specific to research based on the KLoSA, and have been reported for surveys of the elderly population in various countries worldwide, including for the Health and Retirement Study (HRS), ELSA, and SHARE 35 , 36 . More subjective measurements and reports are needed to ensure the reliability and validity, as well as the practical applicability, of the KLoSA questionnaires.…”
Section: Discussionmentioning
confidence: 99%